The Role of Real-Time Tissue Elastography and Gray-Scale Ultrasound Histogram Analysis in the Diagnosis of Patients With Sjögren’s Syndrome - İlhan SEZER,; İclal ERDEM TOSLAK,; Buket YAĞCI,; Funda ERBASAN,; Ayşe AYAN,; Uğur KARASU, (Archives of Rheumatology, 2019)
Objectives: This study aims to evaluate gray-scale histogram analysis of B-mode ultrasound (US) images and US elastographic features of the parotid glands in patients with Sjögren’s syndrome (SS) and to explore relationships with the ultrasonographic and disease activity scores in the light of histopathological findings. Patients and methods: A total of 57 consecutive female patients (mean age 47.9±10.4 years; range 25 to 76 years) with a diagnosis of SS and 48 healthy female individuals (mean age 51.1±10.8 years; range 20 to 70 years) underwent parotid ultrasonography and real-time tissue elastography imaging. Quantitative measurements of gray-scale US images were performed using the histogram software of the scanner. The histogram ratios of the parotid glands from both sides were obtained (histogram ratio; mean gray-scale histogram parotid/mean gray-scale histogram fat). Strain ratio (SR; ratio of fat to gland parenchyma) was calculated from the color-coded images. Subjective B-mode US scoring of electronically recorded gray- scale US images was performed by two radiologists independently for intra- and inter-observer agreement. Subjective assessments, quantitative measurements, and clinical parameters were compared. Results: The SR of the patient group (1.4±0.8 right side, 1.5±0.9 left side) was significantly higher than that of the control group (1.0±0.3 right side, 1.1±0.3 left side) (p<0.05). The gray-scale histogram ratio of the patient group (1.3±0.5 right side, 1.4±0.9 left side) was lower than that of the control group (1.8±0.7 right side, 1.9±0.7 left side) (p<0.05). Receiver-operating-characteristics curve yielded 66% sensitivity for both sides and 50% and 52% specificity for the right and left sides, respectively, for a cut-off SR of 1.02; 76% and 86% sensitivity for the right and left sides, respectively, and 63% specificity for both sides for a cut-off histogram ratio of 1.35. The quantitative histogram ratio method had a higher positivity rate for the diagnosis of abnormal parotid glands than subjective assessments of US images. Conclusion: Sonoelastography and gray-scale histogram analysis of the parotid glands may be used as auxiliary tools to detect parotid gland sonographic abnormalities in patients with SS.